Proyecto de factibilidad para la implementación de una empresa de mudanzas para la ciudad de Quito - Balseca Estrella, Jorge Patricio (2016)
The overall objective of this thesis is to develop a PROJECT FEASIBILITY FOR THE CREATION OF A COMPANY MOVING TO THE CITY OF QUITO, for which we have proceeded to carry out the four main studies that have identified their feasibility, as is the Study Marketing, Technical Study, Organizational Study and Financial Study. In the first instance the deductive, inductive and analytical methods Synthetic based on them perform this research and techniques such as direct observation and market segmentation in this case was the PEA of the city of Quito were analyzed, which is constituted 1,190,632 people with a growth rate of 1.51 % per annum; Data obtained by the NPRI , of which sample size resulting 400 polls applying to said segmentation was performed. In the market study was conducted in the city of Quito, allowed to determine that the project is feasible, the results obtained from the analysis of supply and demand is shown as follows: There is an unmet demand for moving services 1,418,447, which with the launch of the company. The technical study of installed capacity 2,080 Movers determined, but it started with 75% of it in the first year. The company will take its name as movers FOR THE CITY OF QUITO "TOTAL MOVING CIA. LTDA. "And its corporate image logo for identification and rapid market position. It will be marketed directly and the company will adopt a legal form - Management as a LIMITED LIABILITY COMPANY, formed by partners and initially generate jobs between administrative and operational staff. In the financial study the project reaches an investment of $ 45.272,78, and according to financial indicators which indicate favorable for the creation of the company results we have: A positive VAN of $ 169.809,23 dollars, the TIR of 64,17% a RB / C $ 1.29 $ determined that for every dollar invested earnings of $ 0.29 cents was achieved, and the Capital Recovery Period shall be 1 years, 1 month and 30 days, while the sensitivity analysis determined that the project would support an increase of up to 15,95% in its costs and a decrease of 12,75% in revenues. Finally the findings with their recommendations and the accompanying research project were performed.